Hesperidin Attenuates Ultraviolet B-Induced Apoptosis by Mitigating Oxidative Stress in Human Keratinocytes - Hewage, Susara Ruwan Kumara Madduma (Biomol Ther (Seoul), 2016)
Human skin cells undergo pathophysiological processes via generation of reactive oxygen species (ROS) upon excessive exposure to ultraviolet B (UVB) radiation. This study investigated the ability of hesperidin (C(28)H(34)O(15)) to prevent apoptosis due to oxidative stress generated through UVB-induced ROS. Hesperidin significantly scavenged ROS generated by UVB radiation, attenuated the oxidation of cellular macromolecules, established mitochondrial membrane polarization, and prevented the release of cytochrome c into the cytosol. Hesperidin downregulated expression of caspase-9, caspase-3, and Bcl-2-associated X protein, and upregulated expression of B-cell lymphoma 2. Hesperidin absorbed wavelengths of light within the UVB range. In summary, hesperidin shielded human keratinocytes from UVB radiation-induced damage and apoptosis via its antioxidant and UVB absorption properties.